Pendidikan Agama Islam Abad 21 - rohmad (Salimiya: Jurnal Studi Ilmu Keagamaan Islam, 2023)
21st century learning is closely related to the scientific approach very well known to the 5M theory (observing, questioning, collecting data, associating, and communicating). So that in the process of teaching and learning activities are centered on students. In addition, the world of education has a renewal by applying four skills in the 21st century. The skills that must be mastered by students in the 21st century are: communication skills, critical thinking skills, creativity skills, and the skills to collaborate or commonly known as the 4Cs: (Creative, Critical Thinking, Communicative, And Collaborative)